Criminal records and post-prison employment in Ghana: Formal and informal means of performing criminal background checks - Baffour, Frank Darkwa (Criminology & criminal justice, 2023)
This article contributes to the discussion on criminal record-keeping and post-prison employment from the perspective of a developing country. We present and discuss the results of a qualitative research based on interviews with 13 employers in Ghana about the use of criminal background checks in the hiring process. Data suggest a perceived lack of trust towards formerly incarcerated individuals primarily rooted in traditional cultural and moral values. Participants perceived that being associated with people with a criminal record is largely disapproved at the societal level. As a result, formerly incarcerated individuals are discriminated against in the employment setting. We also found that community dynamics and relations manage to overcome the lack of accuracy and reliability of state-provided criminal history information. Due to the absence of reliable access to criminal records through official channels, employers resort to informal means relying on community ties to get access to information about the past and character of job applicants. We conclude by discussing the implications of our findings for research, policy and practice.